Two-phase flow boiling in a microfluidic channel at high mass flux - Keepaiboon, Chanyoot; Dalkilic, Ahmet Selim; Mahian, Omid; Ahn, Ho Seon; Wongwises, Somchai; Mondal, Pranab Kumar; Shadloo, Mostafa Safdari (AIP Publishing, 2020)
We report the experimental investigations of two-phase flow boiling heat transfer characteristics of a refrigerant in a microfluidic channel at a high mass flux (more than 1000 kg/m(2) s). We investigate the heat transfer coefficients at a heat flux range of 7.63 kW/m(2)-49.46 kW/m(2), mass flux range of 600 kg/m(2) s-1400 kg/m(2) s (high mass flux), and saturation temperature range of 23 degrees C-31 degrees C. We propose the new two-phase flow boiling heat transfer correlation of a refrigerant, which is used as the working fluid for the present experiments, at the microfluidic scale. We experimentally establish the functional relationship of two-phase flow boiling heat transfer correlation of the refrigerant during flow boiling in a rectangular microchannel with the Reynolds number, the boiling number, and the Weber number. We believe that the inferences of this study may provide a design basis for the micro-heat exchanger, typically used for thermal management in electronic devices, micro-electro-mechanical systems, and electric vehicle battery cooling system.
Keywords: MICROCHANNEL HEAT SINK; CONTACT LINE DYNAMICS; SHEAR-DRIVEN FLOW; PRESSURE-DROP; LAMINAR-FLOW; VISCOUS DISSIPATION; PARALLEL PLATES; ELECTRIC-FIELD; R134A; PERFORMANCE; Mechanics; Physics